Analysis of product-service system logistics strategies in e-commerce: a literature review - Souza, Nicollas Luiz Schweitzer de; Flores, Maurício Randolfo; Cauchick-Miguel, Paulo Augusto; Frazzon, Enzo Morosini (Brazilian Journal of Operations & Production Management, 2023)
Goal: The main objective of this work is identifying product-service system logistics strategies present in e-commerce. In addition, this research aims to address two main research questions: (i) What are the product-service logistics strategies in e-commerce and how are the strategies applied? and (ii) What are the future research opportunities from the literature? Design / Methodology / Approach: This paper performs a systematic literature review using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. Using this method, we established criteria for inclusion and exclusion of papers as well as better filters that, after applied during the literature review, we reached the final papers that will be included in the analysis. Results: The main opportunity for applying PSS in e-commerce is related to the migration of logistics services to platforms, in which asset sharing between partners is a potential implementation being tested by start-ups and technological companies. Concerning the results related to the association of PSS and e-commerce, this is still a lack in the literature since many papers are more theoretical and fail to assess the benefits of practical adoption. Limitations of the investigation: Research limitations of this research are according to the structure of the systematic literature review methodology. Practical implications: The results may provide guidance for e-commerce retailers that choose to implement PSS strategies associated with logistics in their sales channels. Originality / Value: This paper originality deals with the study of PSS strategies in e-commerce, since the combination of these approaches is still a research gap. Findings point out that e-commerce is still focused on physical products and the adoption of PSS strategies is not a common topic addressed in this context.